Analisa Website Donasi Rumah Tahfizh Menggunakan Metode PIECES - Raja Sultan Firsky; Fadhilah Syafria; Muhammad Affandes; Reski Mai Candra; Lola Oktavia (STMIK Budi Darma, 2023)
One of the many media utilized on the internet is websites. Inadequate website performance, an abundance of irrelevant material, an unappealing website design, confusing navigation menus, and several other issues that influence website quality are issues that are frequently observed on websites. A non-profit organization called Rumah Tahfizh Donation operates a website with the domain donasirumahtahfizh.com that serves as a source of information for both website visitors and donors. The lack of website visitors is a problem Rumah Tahfizh Donation has to face. The more people who visit the website are needed so that more and more people know about the Rumah Tahfizh Donation, the more people want to donate through the Rumah Tahfizh Donation. You can use the PIECES Framework as a guide when creating the website in order to raise its quality. The PIECES Framework is a framework that has categories for dividing up issues and coming up with solutions. According to order, the classification is broken down into six groups: performance, information, economics, control, efficiency, and service. Further testing using the GTMetrix tool is required because the PIECES test has a flaw, notably the inability to acquire a load time score. Additionally, GTMetrix offers a grade that includes a score. The grade and score you receive go up the quicker the website loads